Project management certification : a project management course - Rubio, Mauricio (Packt Publishing, 2018)
"The demand for project managers is increasing at an insane rate as more and more companies realize the importance of this role. This course teaches you all the skills you will need to learn project management and have the best chance at getting the job you want. The author also shares resources you can use to get formally certified for free or at a very low cost by some of the leading universities in the world. He shows you what you need to know and what you have to do, leveraging his experience as a project management expert. Project management positions are growing at 1.5 million opportunities per year and providing exciting career opportunities across industry domains as a project manager, project consultant, project analyst, program manager and project management office manager. Project management is an essential skill-set for many careers and in many contexts in our lives."--Resource description page